2021
DOI: 10.1108/ijbm-09-2020-0465
|View full text |Cite
|
Sign up to set email alerts
|

The influences of technological characteristics and user beliefs on customers' perceptions of live chat usage in mobile banking

Abstract: PurposeIn recent years, numerous banks have introduced live chat systems to their mobile banking (m-banking) applications to help customers address problems that arise while using m-banking. However, few researchers have investigated bank customers' perceptions of live chat in the context of m-banking, known as mobile chat. The present study attempts to fill this research gap and identify potential factors affecting bank customers' intention and attitude toward using mobile chat from the perspective of functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…According to , SI will positively affect user intent to adopt online business. previous research has found that SI has a signi cant relationship on online business performance (Reyes-Mercado, 2018, Chan et al, 2022, Wu and Ho, 2022. According to the above arguments SI is hypothesized to be: H3: Social in uence has a positive relationship with seller's business performance.…”
Section: Social In Uencementioning
confidence: 92%
“…According to , SI will positively affect user intent to adopt online business. previous research has found that SI has a signi cant relationship on online business performance (Reyes-Mercado, 2018, Chan et al, 2022, Wu and Ho, 2022. According to the above arguments SI is hypothesized to be: H3: Social in uence has a positive relationship with seller's business performance.…”
Section: Social In Uencementioning
confidence: 92%
“…The researchers distributed the survey link to young working professionals on social media platforms on personal (FB and WA) and professional (LinkedIn) platforms. The researcher's encouraged participants to share the link with their contacts to ensure wider reach and higher participation, similar to other studies (Scholtz and De Ridder, 2021; Wu and Ho, 2021). The advantage of using the convenience and snowball sampling method is that it serves as an easy way to access a population that the researchers would not be able to tap otherwise.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, m-banking quality has attracted considerable attention from scholars in recent years. Scholars have tried to explore factors affecting m-banking adoption (Saprikis et al, 2022;Souiden et al, 2020;Wu and Ho, 2022), dimensions of its quality (Jun and Palacios, 2016;Shankar et al, 2020Shankar et al, , 2022 as well as the effects of its quality on such positive outcomes as customer satisfaction (De Leon et al, 2020;Khan et al, 2021), positive word of mouth (Rajaobelina et al, 2021), perceived value (De Leon et al, 2020) and value co-creation intentions of the customers (Hijazi, 2022).…”
Section: M-banking Service Quality In Pakistanmentioning
confidence: 99%
“…, 2022; Souiden et al. , 2020; Wu and Ho, 2022), dimensions of its quality (Jun and Palacios, 2016; Shankar et al. , 2020, 2022) as well as the effects of its quality on such positive outcomes as customer satisfaction (De Leon et al.…”
Section: Introductionmentioning
confidence: 99%